Пожалуиста решите уравнения:0,46у-7=0,53у+742-х=72х-432х-1+7=45у-7=11+2у9,6-2,6-х=41,7-0,6у=0,3-0,4у17-4х=5-6х2,8-3,2х=-4,8-5,1х0,25х-2=0,32х-1-0,92у-

Пожалуиста решите уравнения:

0,4(6у-7)=0,5(3у+7)

4(2-х)=7(2х-4)

3(2х-1)+7=4

5у-7=11+2у

9,6-(2,6-х)=4

1,7-0,6у=0,3-0,4у

17-4х=5-6х

2,8-3,2х=-4,8-5,1х

0,2(5х-2)=0,3(2х-1)-0,9

2у-1,5(у-1)=3

1-5(1,5+х)=6-7,5х

3у-18=8у+17

4(1-0,5х)=-2(3+2х)

5х+27=4х+21

у-15=4(3-2у)

  • 0,4(6у-7)=0,5(3у+7)
    4(2-х)=7(2х-4)

    8-4х=14х-28

    -4х-14х=-28-8

    -18х=-36

         х=2

     

    3(2х-1)+7=4

    6х-3+7=4

    6х=4+3-7

    х=0:6

    х=0

     

    5у-7=11+2у

    5у-2у=11+7

    3у=18

      у=6

     

    9,6-(2,6-х)=4

    9,6-2,6+х=4

    х=4-9,6+2,6

    х=-3

     

    1,7-0,6у=0,3-0,4у

    -0,6у+0,4у=0,3-1,7

    -0,2=-1,4

      х=7

     

    17-4х=5-6х

    -4х+6х=5-17

     2х=-12

      х=-6

     

    2,8-3,2х=-4,8-5,1х

    -3,2х+5,1х=-4,8-2,8

    1,9х=-7,6

     х=-4

     

    0,2(5х-2)=0,3(2х-1)-0,9

    х-0,4=0,6х-0,3-0,9

    х-0,6х=-0,3-0,9+0,4

    0,4х=-0,2

       х=-0,5

    2у-1,5(у-1)=3

    2у-1,5у+1,5=3

    0,5у=3-1,5

       у=3

     

    1-5(1,5+х)=6-7,5х

    1-7,5-5х=6-7,5х

    -5х+7,5х=6-1+7,5

     2,5х=12,5

      х=5

     

    3у-18=8у+17

    3у-8у=17+18

    -5у=35

      у=-7

     

     4(1-0,5х)=-2(3+2х)

     4-2х=-6-4х

      -2х+4х=-6-4

        2х=-8

        х=-4

     

    5х+27=4х+21

    5х-4х=21-27

       х=-6

       
    у-15=4(3-2у)

    у-15=12-8у

    у+8у=12+15

    9у=27

     у=3

  • 2,4у-2,8=1,5у+3,5

    2,4у-1,5у=3,5+2,8

    0,9у=6,3

    у=6,3/0,9

    у=7

     

    8-4х=14х-28

    -4х-14х=-28-88

    -18х=-36

    х=36/18

    х=2

     

    6х-3+7=4

    6х=4+3-7

    6х=0

    х=0

     

    5у-2у=11+7

    3у=18

    у=18/3

    у=6

     

    -2,6+х=4-9,6

    х=-3

     

    -0,6у+0,4у=0,3-1,7

    -0,2у=-1,4

    у=1,4/0,2

    у=7

     

    -4х+6х=5-17

    2х=-12

    х=-12/2

    х=-6

     

    -3,2х+5,1х=-4,8-2,8

    1,9х=-7,6

    х=-7,6/1,9

    х=-4

     

    х-0,4=0,6х-0,3-0,9

    х-0,6х=-0,3-0,9+0,4

    0,4х=-0,8

    х=-0,8/0,4

    х=-2

     

    2у-1,5у+1,5=3

    0,5у=3-1,5

    0,5у=1,5

    у=1,5/0,5

    у=3

     

    1-7,5-5х=6-7,5х

    -5х+7,5х=6-1+7,5

    2,5х=12,5

    х=12,5/2,5

    х=5

     

     

    3у-8у=17+18

    -5у=25

    у=25/(-5)

    у=-5

     

    4-2х=-6-4х

    -2х+4х=-6-4

    2х=-10

    х=-10/2

    х=-5

     

    5х-4х=21-27

    х=-6

     

    у-15=12-8у

    у+8у=12+15

    9у=27

    у=27/9

    у=3

     

     

     

     

Комментарии 1

Добавить комментарий

Ваш e-mail не будет опубликован. Обязательные поля помечены *